Atomistic insight into the dislocation nucleation at crystalline/crystalline and crystalline/amorphous interfaces without full symmetry. (1st January 2019) - Xiao, Y.Y.; Kong, X.F.; Yao, B.N.; Legut, D.; Germann, T.C.; Zhang, R.F.
Abstract: Misfit dislocations at bimetal interfaces play a decisive role in determining various deformation behaviors by carrying the shear sliding, serving as a barrier for dislocation transmission and a source of dislocation nucleation. However, when the interface does not possess the distinct feature of misfit dislocations, the nucleation mechanism of lattice dislocations at the interfaces cannot be simply quantified by previously developed atomistic mechanisms based on characteristic misfit dislocations. Using crystalline/crystalline interfaces with a large lattice mismatch and crystalline/amorphous interfaces without local symmetry as prototypes, we show for the first time that the dislocation nucleation at such interfaces is attributable to the localized strain heterogeneities by modifying the volumetric and shear strain components at the atomic level to mechanically respond to different loadings. Using atomic strain tensor analysis, we found that in-plane localized shearing plays a critical role in the emission of lattice dislocations from interfaces, while the corresponding normal components of the volumetric strain tensor will dominate the character of the nucleated lattice dislocation by modifying the atomic excess volume at the interface to overcome the barrier to dislocation nucleation. Further exploration of various crystalline/amorphous interfaces by varying the chemical composition of the amorphous side indicates that chemical heterogeneity may substantially change the strain heterogeneity by forming a different clustered structure at the interface, resulting in the preferred choice of nucleation sites at the boundary regions that can be defined as nano shear traces (NSTs). These results provide a foundation to investigate the effects of strain and chemical heterogeneities in order to provide a realistic explanation of interface mediated deformation mechanisms and an efficient solution to tune interface dominated plasticity. Graphical abstract: Image 1